Knowledge of Contraceptives Among Students in Tertiary Institutions in Anambra State - Ngozi, Orajekwe Veronica (Teaching, Learning, and Development, 2025)
Contraceptive devices are useful in preventing; unwanted pregnancy, preventing sexually transmitted infections and spacing births. The study examines knowledge and use of contraceptive devices among students in tertiary institutions in Anambra State with a view to ascertaining the variables that influence knowledge and use. In line with the objectives of the study, three research questions and two hypotheses were postulated. Descriptive survey research design was adopted. The sample for the study was 600 randomly drawn undergraduate students from three selected tertiary institutions in Anambra State. A structure questionnaire was used for data collection. The instrument had a reliability of 0.86. The data collected were analyzed using descriptive statistics of frequency, percentage and mean as well as inferential statistics of chi-square. The result among others showed that the level of knowledge of contraceptives devices among tertiary institution students in Anambra State is low. Statistical analyses revealed that there is significant relationship among respondent of various -ages and religious affiliations in their knowledge of contraceptive devices.